GR_GERICHTE VR3 2025 22 vom 6. November 2025 , 1. Instanz einzige kantonale Instanz nach 5 Abs. 1 ZPO - GR Gerichte (2025)
Anordnung Ersatzvornahme/Räumung Parzelle Z.1____ | Übrige Fälle und Geschäfte